Development of enzyme-linked immunosorbent assay for the detection of mitragynine and application in electrochemical immunosensor - Mustafa, Radhiahtul Raehan (2021)
Mitragyna speciosa Korth. (kratom) is a tropical plant which has been used since many centuries in traditional human remedies. It contains an alkaloid, i.e., mitragynine, that could render psychotropic effects and is often being misused in substitution for commercial drug. Nowadays, the growing popularity of kratom has led to development of a rapid and effective detection method. Chromatographic methods have been used for the mitragynine detection. The techniques are highly sensitive detection, but they are restricted due to the sophisticated instrument and long-time analysis which is not suitable for routine analysis. Immunoassay has become the standard method for rapid detection of target analyte. They are remarkable for their sensitivity and convenience in sample preparation. Therefore, the main goal of this study was to develop an immunoassay for the detection of mitragynine. To support the main objective, the specific objectives were carried out (1) to extract and purify mitragynine from M. speciosa Korth leaves using solvents with different polarities, (2) to determine reproducibility of mitragynine conjugates using different approach, (3) to develop and optimise enzyme-linked immunosorbent assay (ELISA) with high sensitivity dan specificity detection of mitragynine and (4) to develop and optimise the electrochemical immunosensor for mitragynine based on competitive indirect ELISA. For the first objective, mitragynine extract was obtained using sequential extraction process, whereby solvents with increasing polarities, i.e., hexane, chloroform and methanol were used. Retention factor (Rf) value of mitragynine was identified using thin layer chromatography (TLC) at 0.80 of chloroform and methanol extracts as compared to 0.82 of mitragynine standard. Gas chromatography-mass spectrometry (GC-MS) analysis confirmed the presence of mitragynine in chloroform and methanol extracts. The purity of mitragynine determined based on average intensity ratio of its carbon signals (13C-NMR) to trace impurities which produced 0.075 (g/g) of pure mitragynine. For the second objective, mitragynine molecule was modified at the 16-COOCH3 (methyl ester) and 9-OCH3 (aromatic ether) positions and conjugated to cBSA and OVA forimmunogen and coating antigen, respectively. Successful of mitragynine-protein conjugates had shown by 2,4,6-Trinitrobenzenesulfonic acid (TNBS) which number of bound amino groups for C22-MG-cBSA and C9-MG-cBSA were 45 and 46, respectively. Fourier transform infrared spectroscopy (FTIR) showed the changes of the spectra at C22-hydroxymitragynine and C9-hydroxymitragynine as compared to the mitragynine, indicates a successful reduction and demethylation process, respectively. UV-Vis spectra showed successful conjugates with quantitative changes in the spectral region of 240–300 nm for conjugated mitragynine to cBSA and OVA. For the third objective, the immunogens were immunised into rabbits (n=2 for each immunogen) for polyclonal antibody (pAb) production. Binding affinity of anti-sera and purified IgG were examined using indirect ELISA. The affinity of purified IgGs from rabbits immunised with C22-MG-cBSA showed mean Kd of 7.965 × 10-6 μM, which was significantly higher affinity (p < 0.05) than those immunised with C9- MG-cBSA at Kd of 1.390 × 10-4 μM. The mitragynine immunoassay showed a limit of detection (LOD) and limit of quantification (LOQ) of 0.412 μg/mL and 1.25 μg/mL, respectively. The measurement range was between 0.01 to 100.0 μg/mL and minimal inhibition (IC50) value of 0.152 μg/mL. For the final objective, optimum ELISA system was applied in electrochemical immunosensor to enhance sensitivity detection of mitragynine. Differential pulse voltammetry (DPV) analysis showed that, the detection potential immunosensor of mitragynine was confirmed at +0.25 ± 0.1 V. Non-linear calibration curve was in the range of 0-50 μg/mL. A 10-fold higher sensitivity was obtained using electrochemical immunosensor system with LOD and LOQ at 0.018 and 0.06 μg/mL, respectively and IC50 of 0.097 μg/mL. Electrochemical immunosensor also showed a good precision with reproducibility of 6.2%, repeatability of 9.5% and acceptable recovery range of 93 to 113%. In conclusion, an immunoassay was successfully developed with high sensitivity and specificity detection of mitragynine. The finding of this study can potentially be improved with increase the hapten numbers (i.e., 10-20 molar ratio) for optimal coupling rate, highly immunogenic carrier protein such as keyhole limpet hemocyanin (KLH) and suitable spacer arm with appropriate length (i.e, 3-6 carbon) which is not too short or long.